First record of shrews (Eulipotyphla, Soricidae) in the Sierra de Otontepec, an isolated mountain in Veracruz, Mexico - Mayen-Zaragoza, Marco; Guevara, Lázaro; Hernández-Canchola, Giovani; León-Paniagua, Livia (THERYA, 2019)
Knowledge of the diversity and distribution of mammals in tropical and subtropical regions remains incomplete. This is especially true for many small species inhabiting remote areas with limited access. Here we present the first record of small-eared shrews (Soricidae, Cryptotis) from the Sierra de Otontepec, Mexico, an isolated mountain in the Gulf Coastal Plain that has remained poorly explored (Figure 1). We conducted a short-term survey in the Sierra de Otontepec using pitfall and Sherman traps during August 2016. Taxonomic identification was based on morphological and molecular analyses (Appendix 1). We collected six shrew specimens from the cloud forests in the Sierra de Otontepec (Figure 2). Morphological and molecular characterization indicated that all specimens collected were small-eared shrews belonging to the Cryptotis mexicanus species group (Table 1, Figure 3), a clade which is closely associated with cloud forests. Based on the morphological and molecular evidence, we refer to this population from the Sierra de Otontepec as C. mexicanus, Our results corroborate the importance of continued fieldwork in remote tropical areas. Overall, this finding offers relevant information that could be used to better understand the evolution and biogeographic history of this species group and its habitat.